2021
DOI: 10.3390/su13084321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silica Fume as a Waste Material for Sustainable Environment on the Stabilization and Dynamic Behavior of Dispersive Soil

Abstract: The use of dispersive soils, which are common in many parts of the world, in engineering applications such as water structures, earthen dams and road embankments is possible with their improvement. Recently, the effects of different chemicals on the stabilization of dispersive soils have been investigated. The use of waste materials in stabilization is preferred both because of the more sustainable environment and the economic advantages it provides. The use of silica fume (SF) as a waste material in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 46 publications
(49 reference statements)
2
4
0
Order By: Relevance
“…Further addition of ESA in kaolinite clay-SF mix leads to a reduction in the UCS, while additional L in kaolinite clay-SF mix results in a significant increment in the UCS. Similar observations were made by Türköz et al [23], Phanikumar et al [24], and Yuan et al [25]. The findings indicate that the application of SF-ESA-L resulted in a substantial increase in UCS, with strength improvement reaching up to 81.03% (69.344 kN/m²).…”
Section: Unconfined Compression Testsupporting
confidence: 87%
“…Further addition of ESA in kaolinite clay-SF mix leads to a reduction in the UCS, while additional L in kaolinite clay-SF mix results in a significant increment in the UCS. Similar observations were made by Türköz et al [23], Phanikumar et al [24], and Yuan et al [25]. The findings indicate that the application of SF-ESA-L resulted in a substantial increase in UCS, with strength improvement reaching up to 81.03% (69.344 kN/m²).…”
Section: Unconfined Compression Testsupporting
confidence: 87%
“…While at 28 days and 90 days, the compressive strength of concrete prepared using UFS containing 20% FA activated with 4% sodium oxide equivalent (Na 2 O-E) of sodium sulphate (NS) reached up to 41.5 MPa and 60.8 MPa, respectively, as shown in Fig. 16. In comparison with the typical alkaliactivated system, CO 2 emissions from sodium silicateactivated slag/FA were reduced to 53-72 kg/t, a reduction of 45-64 per cent [73].…”
Section: Ultra-fine Slagmentioning
confidence: 95%
“…According to "CemWeek research's 2020 update of the Global Ground Granulated Blast Furnace Slag Market Report and Forecast", total amount of GGBS production is about to reach 269 million tonnes between 2020 and 2025, while fly ash production which was 225 million tonnes in year 2020 would also drastically increase [15]. The silica fume produced globally every year is around 1 million tonnes [16], while by-products such as metakaolin, ferrochrome slag, and ultra-fine slag contribute to the remaining portion of industrial wastes produced, as shown in Fig. 3a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method aims to meet the specific needs of well-graded soil, which ultimately improves the properties of the soil [19], [20][21][22]. Chemical stabilization of soil is the process of adding soil stabilizer admixture such as cement, lime or industrial wastes with the clay soil to improve the characteristics of soft clay, which its durability and shear strength [4], [23][24][25]. In this research, palm oil fuel ash (POFA) and lime are mixed into soft clay to enhance its strength properties.…”
Section: Introductionmentioning
confidence: 99%